Trial and testimony of sense of guilt in Nina Yargekov’s Vous serez mes témoins (Comparatismi, 2023)
Since the last decades of the 20th century, there has been a growing interest in the study of emotions. The emotional turn (T. Anz 1999) has not only involved psychology (K. Oatley 2004, P. Ekman 2003, K. Scherer 2009) but is a true interdisciplinary approach (Affective Sciences). The sense of guilt, first studied in psychology by Freud in Mourning and Melancholy (1917), is a complex secondary emotion (C. Izard 1977) that is generated by the relationship with society and its norms and is therefore defined as self-reflexive, for it implies that the individual reflects on him/herself within his/her social context. In Vous serez mes témoins (2011), the French-Hungarian writer Nina Yargekov approaches the theme of the sense of guilt over the suicide death of her best friend Élodie. Balancing between a court testimony and a diary of mourning, the novel tells the story of a court trial where the narrator is accused of an unusual fraud: the simulation of mourning. The novel becomes simultaneously the courthouse and the diary in which to record the sense of guilt in a neurotic and chaotic manner. A painful writing full of fiction and humour, which thanks to the skilful use of parody and pastiche makes possible the literary transposition of what can hardly be said and understood.
Keywords: Nina Yargekov; Secondary Emotion; Sense of Guilty; Autofiction; Trial